Kendall's advanced theory of statistics: Volume 2B, Bayesian inference - O'Hagan, Anthony (London : E. Arnold, 1994)
Cross-references within this volume follow the established practice of Kendall's Advanced Theory of Statistics.
Volume 2B
osc 1/11/2021
Loans
Keywords: Mathematical statistics; Bayesian statistical decision theory